The Role of Tracer Studies in Enhancing the Quality of Education: A Case in State Islamic Higher Education - Noor Saif Muhammad; Siti Rohaya; Anwar, Moh. Khoerul (International Journal of Applied Guidance and Counseling, 2024)
A key factor in creating and improving higher education quality is data and information from tracer studies, which are also alumni feedback. Nowadays, educational institutions must to generate graduates with both academic proficiency and practical work-related abilities. This study aims to determine the extent to which the role of tracer studies in improving the quality of study programs at UIN Sunan Kalijaga. The survey approach is being used in this descriptive qualitative study. It can be inferred from survey results that data and information from tracer studies can be used as a medium for quality improvement study programs at UIN Sunan Kalijaga. These indicators included aspects of lecture activities and facilities, aspects of foreign languages, aspects of learning experiences that support work, and aspects of graduate competence.